Аналітичне дослідження формування параметрів виробів при комбінованому активному контролі - Сеник, В. В. (Видавництво Державного університету "Львівська політехніка", 2000)
The paper presents the analitical investigation of the methods of products manufacture technological accuracy while using combinated control monitoring.